Palladium‐Catalyzed Reductive Carbonylation of (Hetero) Aryl Halides and Triflates Using Cobalt Carbonyl as CO Source. Issue 2 (22nd December 2020) - Dogga, Bhushanarao; Kumar, C. S. Ananda; Joseph, Jayan T.
Abstract: An efficient protocol for the reductive carbonylation of (hetero) aryl halides and triflates under CO gas‐free conditions using Pd/Co2 (CO)8 and triethylsilane has been developed. The mild reaction conditions, enhanced chemoselectivity and, easy access to heterocyclic and vinyl carboxaldehydes highlights its importance in organic synthesis. Abstract : A generalized protocol for the reductive carbonylation of (hetero) aryl halides and triflates under CO gas‐free conditions using Pd/Co2 (CO)8 and triethylsilane has been developed. The mild reaction conditions, enhanced safety, and wide substrate scope highlight its importance in routine organic synthesis.